Alterations in Cerebral Blood Flow after Resuscitation from Cardiac Arrest - Iordanova, Bistra; Li, Lingjue; Clark, Robert S. B.; Manole, Mioara D. (Frontiers in Pediatrics, 2017)
Greater than 50% of patients successfully resuscitated from cardiac arrest have evidence of neurological disability. Numerous studies in children and adults, as well as in animal models have demonstrated that cerebral blood flow is impaired after cardiac arrest. Stages of cerebral perfusion post-resuscitation include early hyperemia, followed by hypoperfusion, and finally either resolution of normal blood flow or protracted hyperemia. At the level of the microcirculation the blood flow is heterogeneous, with areas of no flow, low flow, and increased flow. Cerebral blood flow directed therapies in animal models of cardiac arrest improved neurological outcome, and therefore the alterations in cerebral blood flow after cardiac arrest likely contribute to the development of hypoxic ischemic encephalopathy. Current intensive care after cardiac arrest is centered upon maintaining systemic oxygenation, normal blood pressure values for age, maintaining general homeostasis, and avoiding hyperthermia, Assessment of cerebral blood flow and oxygenation is not routinely performed after cardiac arrest. Currently available and underutilized techniques to assess cerebral perfusion include transcranial doppler, near infrared spectroscopy, and arterial spin label magnetic resonance imaging. Limited clinical studies established the role of cerebral blood flow and oxygenation monitoring in prognostication after cardiac arrest and few studies suggest that guiding critical care post-resuscitation to mean arterial pressures above the minimal autoregulatory range might improve outcome. Important knowledge gaps thus remain in cerebral monitoring and cerebral blood flow and oxygen goal-directed therapies post-resuscitation from cardiac arrest.